Study of serum gamma glutamyl transferase in acute stroke - a single centre experience - Mulakalapalli, Vijay K.; Pallekonda, Elicin D.; Nadimi, Tejasri; Kaushal, Yuvraj; Gummalla, Vaishnavi; Velusamy, Breethiga; Thakwani, Mahek; Katikala, Venkata R.; Rathore, Anshita (International Journal of Advances in Medicine, 2024)
Background: Gamma-glutamyl transferase (GGT) is an enzyme involved in oxidative stress and inflammation, which are key mechanisms in the pathogenesis of stroke. Recent evidence suggests serum GGT levels may be associated with the risk and prognosis of acute ischemic stroke. This study aimed to investigate serum GGT levels in patients with acute stroke at a single center in India. Methods: This case-control study included 100 patients (50 with acute stroke and 50 age and sex-matched controls). Patients aged 40 to 80 years and diagnosed with acute stroke (encompassing first-time occurrences of intracerebral hemorrhage, ischemic stroke, and subarachnoid hemorrhage) were included in the study. Serum GGT levels were compared between stroke patients and controls. The association of GGT with various risk factors was also analyzed among cases. Results: The mean age of cases is 60.2±10.07 years. Hemorrhagic stroke was most common and found in 52% of cases. Mean serum GGT levels were significantly higher in stroke patients (55.2540±40.8909 U/l). Higher serum GGT levels were associated with male gender, presence of diabetes, hypertension, dyslipidemia and smoking and were found to be statistically significant (p<0.005). Age and stroke type were found to be not significantly associated with GGT levels. Conclusions: In conclusion, our study findings indicate that elevated serum GGT levels are associated with an increased risk of stroke, particularly in male patients and those with hypertension, dyslipidemia, and diabetes. Further prospective studies are needed to establish the predictive value of GGT for stroke.